Full steam ahead: A history of the Tiwi geothermal power plant, 1962-2023 - Villanueva, Arvi J. (Animo Repository, 2024)
This study is about the history and development of the Tiwi Geothermal Power Plant. It creates a historical narrative of the Tiwi Geothermal Power Plant as an institution starting from the initial geothermal studies conducted in Tiwi, Albay in 1962 to its development in 1972; its operationalization in 1979, the reform and modernization of the country’s electric industry in 2001; and the recent developments in geothermal energy in 2023. As part of the historical narrative, the study also examines the Tiwi Geothermal Power Plant’s contributions to the Philippine geothermal industry as a trailblazer and its effects on the Municipality of Tiwi and the local community.